Embedded Game Design as a Method for Addressing Social Determinants of Health. Issue 3 (3rd July 2018) - Gilliam, Melissa; Jagoda, Patrick; Jones, Ian Bryce; Rowley, Jennifer; Hill, Brandon
ABSTRACT: This paper, describes the design, development, and evaluation of The Test, a theory-based mobile game prototype designed to promote HIV testing by providing information and influencing motivations, and behavioral intentions among YMSM. The Test was designed using embedded design, first described by Kaufman & Flanagan (2015), which diverges from traditional "educational game" design strategies by mixing on-message content with nonfocal content, in an attempt to make the overall experience more approachable and engaging. One challenge of embedded design is that it targets attitudes and actions that are not always proximate to a particular behavior. Games with embedded content forgo explicit takeaways, and their possible distal effects present a challenge to traditional tests of efficacy. The benefit of embedded design, however, is that its holistic or ecological design approach (which considers feelings, emotions, affects, social relations, and connections to broader communities) stands in close alignment with the social-ecological model.